Habanera, Sonatina, Malambo e Carnavalito de Salvador Amato: aspectos históricos, analíticos e edições de performance. - Rodrigo Guillermo Olivárez Olivares (2015)
Study about four works for double bass and piano (Habanera, Sonatina, Malambo and Carnavalito) by Argentinean composer-bassist-pedagogue Salvador Amato (1928-1994). It includes historical, stylistic, pedagogical and idiomatic writing information on Amatos music. A thorough analysis of the manuscripts shows not only an important idiomatic writing for the double bass repertory, with its pedagogical aspects, but also notational inconsistencies and errors. Interviews with Amatos ex-students reveal performance practices that are not notated in the scores, but transmitted through oral tradition. The analytical data served as the basis for the preparation of the performance editions of the works, presented at the end with the broader goal to rescue Amatos history and music.